1992
DOI: 10.1139/v92-197
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine in mineral soil: chemical species and catalysed hydrolysis

Abstract: Equilibrium and kinetics parameters have been evaluated at 25.0 °C for the heterogeneous catalysis of atrazine hydrolysis in slurries of a chemically characterized mineral soil. The fraction of acidic sites that accounts for sorption capacity, and the sorption equilibrium function resemble those for humic acid and organic soil. Sorption and desorption half-lives increased with increasing coverage of sorption sites. The sorption half-lives ranged from 3.6 to 735 days. The desorption half-lives ranged from 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
(25 reference statements)
0
31
2
Order By: Relevance
“…Therefore we conclude that one set of parameters can be successfully used to describe atrazine behavior over this C i range. Table 1 is one order of magnitude greater than the hydrolysis constant for a mineral soil (1.72 x 10 -4 hours-i), as reported by Gamble and Khan [1992]. The reason for this discrepancy may be due to the assumption that this irreversible coefficient is a "lumped" constant which accounts for both chemical degradation as well as possible irreversible reac-…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore we conclude that one set of parameters can be successfully used to describe atrazine behavior over this C i range. Table 1 is one order of magnitude greater than the hydrolysis constant for a mineral soil (1.72 x 10 -4 hours-i), as reported by Gamble and Khan [1992]. The reason for this discrepancy may be due to the assumption that this irreversible coefficient is a "lumped" constant which accounts for both chemical degradation as well as possible irreversible reac-…”
Section: Resultsmentioning
confidence: 81%
“…Therefore it is not easy from our data base to achieve a set of model parameters which can fully describe atrazine adsorptiondeso•tion over a wide concentration range. In fact, Gamble and Khan [1992] found that values for atrazine adsorptiondesorption rate coefficients decreased as the amount of the atrazine adsorption sites approached saturation. They also found that a mass balance loss, referred to as bound residue, increased as atrazine concentration decreased.…”
Section: Attempts To Describe Atrazine Adsorption and Desorption Isotmentioning
confidence: 99%
“…In addition, prefiltered solutions are injected for simple analysis of the soluble pesticide. Details of the method and equipment have been described elsewhere (Gamble and Khan 1992).…”
Section: The Rp-hplc On-line Microfiltration Methodsmentioning
confidence: 99%
“…Proof of concept has been published for the experimentally supported theory that reveals the kinetics and mechanisms of pesticides in soil and water [1][2][3][4][5][6][7][8][9]. For a soil immersed in a pesticide solution, the starting point was the answer to a critical question.…”
Section: What Has Been Donementioning
confidence: 99%